Lizard Island Polychaete Workshop: sampling sites and a checklist of polychaetes - Ribas, Julia; Hutchings, Pat (Zootaxa, 2015)
In August 2013, a two week polychaete workshop was held at Lizard Island, Great Barrier Reef. Twenty-one sites representing 121 collection events were sampled for polychetes around Lizard and on the Outer Barrier. Workshop participants sorted polychaetes to family and each participant received on loan selected families to work up. This Zootaxa monograph describes 91 new species, 67 new records for Lizard Island, and 19 for Australia. Details regarding the habitats and locations are provided in Table 2 together with two maps (Figs 1, 2) showing sampling locations. In this paper we also list previously collected polychaete material from the region together with any published records for families which are not included in this volume.